No structural brain alterations in new daily persistent headache – a cross sectional VBM/SBM study. (April 2022) - Naegel, Steffen; Zeller, Julia; Hougard, Anders; Weise, Christopher Michael; ,; Zuelow, Stefan; Kleinschnitz, Christoph; Obermann, Mark; Solbach, Kasja; Holle, Dagny
Objective: To identify grey matter alterations in patients suffering new daily persistent headache to enrich the pathophysiological concept of this rare headache disorder characterised by a distinct, clearly remembered onset and its instant chronification. Method: Magnetic resonance-based voxel-based and surface-based morphometry was used to investigate 23 patients suffering from new daily persistent headache and 23 age- and gender-matched healthy controls with 1.5 Tesla MRI. Independent statistical analysis was performed at three sites using statistical parametric mapping, as well as FSL(FMRIB Software Library)-based approaches. Results: No grey matter changes were detected using this sophisticated and cross-checked method. Conclusion: The absence of structural brain changes in patients with new daily persistent headache contribute to the recent discussion regarding structural alterations in primary headache disorders in general and does not provide evidence for grey matter changes being associated with the pathophysiology of new daily persistent headache. Future research will have to determine the underlying pathophysiological mechanisms of this disorder.